Assessment of Knowledge and Adoption of Drip Irrigation in Cotton Crop among Farmers of Haryana - Kumari, Vinod; Chander, Subhash; Malik, Karmal; Kaur, Bas (Indian Journal of Extension Education, 2022)
The study was set about in the state of Haryana to gauge the knowledge and adoption level of the drip irrigation system (DIS) in the cotton crop amongst the farmers. The research highlighted that more than two-thirds of the farmers (68.33%) had a high level of knowledge of DIS. The socio-economic factors such as the family income, size of the landholdings, exposure to the mass media, education level and the socio-economic status of the respondents were significantly correlated with the overall levels of knowledge and adoption of DIS by the farmers. On a whole, more concentrated efforts are the call of the hour to increase the knowledge levels and adoption of micro irrigation techniques on a wider scale.
Keywords: Drip irrigation system; Knowledge and adoption; Socio-economic factors; Cotton crop